Crossing Lines: the Chisholm Trail, the Railroads, and the Flint Hills - Christy Davis (Symphony in the Flint Hills, 2017)
Introduction: The nineteenth century created the cattle business, but it also created cattle, or at least what we recognize as cattle today. Before then, bovines were products of their environments, giving each region a breed that had adapted to its local climate and vegetation. Then, in the spirit of “animal husbandry,” Victorians sought out and bred cattle that were built for one purpose: to produce beef.
Keywords: railroad impact; cattle markets; cattle trade; Texas fever; Kansas; Flint Hills; cattle disease; 19th century; quarantine; Sam Wood